Testing Weak Form of Market Efficiency by Application of Simple Technical Trading rules on the Indian Stock Market - Agarwal, Ankit (2006)
The efficient market hypothesis has been and continues to be one of the most contentious issues in finance. The studies conducted till 1960's and 1970's fairly supported EMH until recent years, when some academicians proved that the theory is not applicable in real markets. This was done either by using statistical tests or by testing with simple technical trading rules. In this two of the most popular trading rules have been used to test the efficiency of Indian stock markets. The trading rules used in this study are moving average rule and trading range break out rule. In the study it has been proved that the technical trading rules work well in the Indian stock markets even after considering transaction costs. Hence the Indian markets are still not weak form efficient.